The costs of participation in and delivery of community sport in Australia—a narrative review - Westerbeek, Hans; Eime, Rochelle; Owen, Katherine (Frontiers in Sports and Active Living, 2025)
Rising financial costs are undermining equitable access to community sport and threatening the sustainability of grassroots delivery systems. This narrative review synthesises peer-reviewed and grey literature, focusing on the Australian context, to examine the costs of participating in and delivering community sport. Evidence confirms that affordability remains a persistent barrier across all age groups, disproportionately affecting low socio-economic populations, culturally diverse groups, Indigenous communities, and people with disabilities. In parallel, community sports clubs are challenged by escalating facility, insurance, and staffing costs, declining volunteer numbers, and uncertain revenues, resulting in increasing reliance on participant fees and short-term fundraising. Strategies to reduce financial barriers include voucher schemes, tax rebates, grant programs, and charity-based initiatives. While these interventions provide temporary relief, they often benefit higher-income families more and rarely achieve long-term participation sustainability. Comparative international insights highlight that structural differences in funding models, ranging from heavily subsidised European systems to pay-to-play models in the United States, shape affordability and access in distinct ways. Policy implications point to the need to reposition community sport as a public good embedded in preventive health and equity frameworks, rather than as a consumer service. Achieving inclusive and sustainable systems requires moving beyond universal supports toward equity-focused, co-designed solutions that target priority groups, enhance club capacity, and also recognise the role of informal sport in providing low-cost opportunities. Future research should evaluate the long-term impact of financial interventions, develop robust economic models of return on investment, and examine the potential of digital innovation to alleviate cost pressures.